Synthesis and Characterization of Ammonium Acesulfamate - Echeverría, Gustavo Alberto (2014)
Ammonium acesulfamate, (NH4)C4H4NO4S, was prepared by the reaction of acesulfamic acid and ammonium carbonate in aqueous solution, and characterized by elemental analysis and 1H and 13C NMR spectroscopy. Its crystal and molecular structure was determined by single-crystal X-ray diffraction methods. The substance crystallizes in the orthorhombic space group Pnma with Z = 4 molecules per unit cell. The NH4 + ion generates medium to strong hydrogen bonds with the carbonylic oxygen, the iminic nitrogen and the sulfonyl oxygen atoms of the acesulfamate anion. The FTIR spectrum of the compound was also recorded and is briefly discussed.